Indonesian ministry of tourism and creative economy and the crisis frame related to COVID-19 - Adiprasetio, Justito; Wibowo, Kunto Adi; Fauzi, Muhammad Ilham; Aliifa, Dzikrifa Ningtyas (PRofesi Humas, 2023)
Background: The COVID-19 pandemic has forced governments worldwide to mitigate the tourism sector’s crisis, one of which is to rely on effective and efficient crisis communication. However, the Indonesian government, particularly the Ministry of Tourism and Creative Economy (Kemenparekraf), has been accused of being incompetent in managing its crisis communications. The COVID-19 pandemic has forced governments worldwide to mitigate the tourism sector’s crisis, one of which is to rely on effective and efficient crisis communication. Even so, no study shows how the Indonesian Ministry of Tourism and Creative Economy crisis communication was carried out in the early phase of the pandemic. Purpose: This study aims to examine how crisis communication was carried out by the Indonesian Ministry of Tourism and Creative Economy in the early phase of the pandemic. Methods: This study used the quantitative framing analysis method to examine the crisis frame in 178 press releases published on the official website of the Kemenparekraf in January 2020-May 2020. Results: The economic frame ranked second only behind the attribution of responsibilities and was more dominant than the human interest and morality frame. There was a public response where the government, especially the Kemenparekraf, is considered as only prioritizing economic over public safety. Conclusion: This study found that in the world’s initial phase of the COVID-19 outbreak, the press release published by the Kemenparekraf did not represent an effort to prevent and control the spread of COVID-19 in Indonesia since it would have a significant impact on the tourism sector. Implications: Furthermore, the Kemenparekraf needed to optimize the call to action message to positively influence the public and tourism actors and assist efforts to respond to the COVID-19 pandemic crisis.